Foursquare, the Politics of Location Platforms, and the Importance of Geocoded Data - Wilken, Rowan Cameron (AoIR Selected Papers of Internet Research, 2013)
This paper takes a political economic and “platform politics” approach in examining the shifting business model of mobile social networking service Foursquare. Working from an understanding that medium (or platform) specificity still matters, it explores how Foursquare’s shifting business model is driving changes in location data generated by its users is extracted, handled, and “monetized”.